PELATIHAN AI WRITING TOOLS UNTUK MELATIH WRITING SKILLS BAGI SISWA SMP DI TORAJA UTARA - Fansury, Andi Hamzah; Rampeng, Rampeng; Batau, St. Haliah; Moelier, Dahlia D.; Asyrafunnisa, Asyrafunnisa (TONGKONAN: JURNAL PENGABDIAN MASYARAKAT, 2023)
The implementation of this training is in partnership with SMPN 2 Sesean students in the south Pangli district, Sesean district. This training aimed to introduce AI writing tools to the target partners so that their writing skills in English could develop. The team did their training because leaving the problem of secondary school students Sesean had not yet been interested in writing tools because junior high school students had not yet been required to master and apply their special writing skills in English. PKM activities are conducted with preparation, socialization, training and counseling, and evaluation. As for the results of a training program involving ten students: (1) Students can be able to use ai writing tools (Quilbot and Grammarly), (2) Students can draw on artificial intelligence writing technology in English writing tools, (3) Students can develop their writing ability by using ai writing tools until their writing skills can be more optimal and can be applied to further education.